Development of an Intranasal In Situ System for Ribavirin Delivery: In Vitro and In Vivo Evaluation - Iosif B. Mikhel; Elena O. Bakhrushina; Danila A. Petrusevich; Andrey A. Nedorubov; Svetlana A. Appolonova; Natalia E. Moskaleva; Natalia B. Demina; Svetlana I. Kosenkova; Mikhail A. Parshenkov; Ivan I. Krasnyuk; Ivan I. Krasnyuk (MDPI AG, 2024)
Recently, ribavirin has demonstrated effectiveness in treating glioblastoma through intranasal administration utilizing the nose-to-brain delivery route. Enhancing ribavirin's bioavailability can be achieved by utilizing intranasal stimuli-responsive systems that create a gel on the nasal mucosa. The research examined thermosensitive, pH-sensitive, and ion-selective polymers in various combinations and concentrations, chosen in line with the current Quality by Design (QbD) approach in pharmaceutical development. Following a thorough assessment of key parameters, the optimal composition of gellan gum at 0.5%, Poloxamer 124 at 2%, and purified water with ribavirin concentration at 100 mg/mL was formulated and subjected to in vivo testing. Through experiments on male rats, the nose-to-brain penetration mechanism of the active pharmaceutical ingredient (API) was elucidated, showcasing drug accumulation in the olfactory bulbs and brain.